A video data analysis of pet theft incidents: an examination of offense form, situational dynamics, & offender characteristics - Stickle, Benjamin F. (Deviant behavior, 2025)
Pet theft is a type of property crime, but pet-owner relationships include emotional dimensions and life experiences that can compound their loss far beyond property value. Their bondedness with humans includes companionship as well as healthy lifestyle and mental wellness benefits, which are abruptly halted at junctures of pet loss. Though pets are stolen for various motives (e.g. ransom, reward, resale, or breeding), this crime form has received little research attention from academic criminology and criminal justice. Toward building a line of inquiry, this paper empirically explores the phenomena of "dognapping" as dogs are the most frequently stolen pet and the only pet for which there is a database large enough for meaningful exploration. Content analysis of online posts and web-based video data (Twitter/X1 posts, YouTube videos, and social media websites dedicated to missing and stolen pets) enabled a delineation of dog theft forms, offense dynamics, and offender characteristics. Findings regarding residential and commercial dog theft center discussion on situational crime prevention implications and additional research opportunities to further evidence and explore this relatively disregarded crime.